The Contribution Of Agricultural Extension Workers To Honey Citrus Farming Income In Improving Regional Superior Products - Zainol Arifin; Rita Alfin; Listiyana (International Journal of Business and Quality Research, 2025)
The purpose of this study is to analyze the extent of the role of agricultural extension officers in increasing the income of Siamese orange farmers. The research was conducted in Dau Subdistrict, Malang Regency, involving 35 respondents of chayote farmers who are members of farmer groups. The study used a descriptive quantitative approach and data collection was conducted through questionnaires, interviews, and observations. The three main roles of extension agents analyzed were as facilitators, motivators, and dynamists. The results showed that the contribution of agricultural extension workers was high, with a contribution score as a facilitator of 61.02%, as a motivator of 62.85%, and as a dynamizer of 64.68%, all of which fell into the category of "contributing." Extension agents are proven to play a role in technical training, providing motivation, and encouraging farmers to be more active and innovative in developing their businesses. In terms of economics, siamese orange farming generates a net income of Rp54,759,259 per hectare with an R/C ratio of 1.652, which means that the business is financially viable even though profits are relatively modest.